The rights of unmarried cohabitants in Canada. Issue 1 (19th December 2017) - Brown, Catherine; Gardiner, Kyle T
Abstract: The number of unmarried, cohabitating couples in Canada has increased steadily over the past 50 years. The rights and remedies that flow from these relationships vary widely across Canada's provinces and territories. 1 The authors survey the laws of four provinces (British Columbia, Alberta, Ontario, and Quebec) as illustrative in three distinct areas: property rights, spousal support, and rights on a partner's intestate death. Tax issues arising in these three areas are also considered.